Evaluation of phosphate sources using ruminal fiber transit kinetics methodology - Couto, Claudiney de Jesus; Braga, Bruna Cardoso; Gomes, Raphael dos Santos; Tamy, Wagner Pessanha; Villela, Severino Delmar Junqueira; Leonel, Fernando de Paula (Frontiers in Animal Science, 2025)
IntroductionSince the low phosphorus content is one of the reasons for the low degradation of fiber in roughage such as pasture and by-products, fiber transit kinetics can be an important tool to evaluate differences in digestion depending on phosphorus supplementation with different sources. The objective was to compare the potential of different sources of phosphorus in promoting improvement in fiber digestibility parameters.MethodsFeeds low in phosphorus were chosen to compose the basal diet. Five crossbred heifers with an average initial weight of 150 ± 8.2 kg were used, randomly distributed in a 5x5 Latin square. The treatments were: negative control (NC) without supplementary phosphorus; dicalcium phosphate from igneous rock with sulfuric acidulation, neutralization with limestone, and the show physical form of microgranules (ISLG); Dicalcium phosphate from igneous rock with sulfuric acidulation, neutralization with hydrated lime, and the physical form of powder (ISLhP); Dicalcium phosphate from sedimentary rock with hydrochloric acidulation, neutralization with limestone, and the micro-granulated show physical form (SeCLG); Dicalcium phosphate from the monocalcium phosphate and hydrated lime reaction adjusted with phosphoric acid, and the powder physical form (MLhPaP). The parameters of the kinetics transit of particles with use of the chromium marker, fixed to the roughage cell wall and subsequent recovery of the marker in the heifer feces, were determined.Results and discussionThe ISLG resulted in a higher (p<0.05) passage rate of particles from the solid to the liquid phase in the rumen-reticulum. There was no difference (p>0.05) between the diets for the time that indigestible particles spent from ruminal escape to their first appearance in feces. The longest retention time (p<0.05) of solid particles in the rumen-reticulum was detected in animals that received NC diet. In conclusion, heifers that do not receive supplemental phosphorus exhibited poorer fiber processing and dry matter intake (DMI).